2020
DOI: 10.1182/hematology.2020000121
|View full text |Cite
|
Sign up to set email alerts
|

Management of Waldenström macroglobulinemia in 2020

Abstract: The management of Waldenström macroglobulinemia (WM) has evolved tremendously with recent genomic discoveries that correlate with clinical presentation and could help to tailor treatment approaches. The current diagnosis of WM requires clinicopathological criteria, including bone marrow involvement by lymphoplasmacytic lymphoma cells, a serum immunoglobulin M (IgM) monoclonal paraprotein, and presence of the MYD88 L265P mutation. Once the diagnosis is established, the relationship between the patient’s symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Based on these data, ibrutinib and other BTK inhibitors have become the preferred CLL treatment to date. A similar development has taken place in Waldenström's macroglobulinemia, WM (14).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Based on these data, ibrutinib and other BTK inhibitors have become the preferred CLL treatment to date. A similar development has taken place in Waldenström's macroglobulinemia, WM (14).…”
Section: Introductionsupporting
confidence: 55%
“…The C481 mutants are not exclusively seen during ibrutinib treatment, they are also found in patients treated with other irreversible BTKi that target C481, namely acalabrutinib ( 57 ) and zanubrutinib ( 58 ). Furthermore, resistance mutations not only appear in CLL, but also in MCL ( 59 ), marginal zone leukemia (MZL) ( 60 ) and Waldenström’s macroglobulinemia ( 14 , 61 ).…”
Section: Resistance Mutations Predominantly Affect Btkmentioning
confidence: 99%
“…Importantly, a multinational phase I/II study demonstrated the efficacy of acalabrutinib in ibrutinibintolerant CLL patients, verifying its reduced toxicities compared to ibrutinib (Isaac and Mato, 2020). Clinical trials have also shown the efficacy of acalabrutinib monotherapy in patients with WM (Castillo et al, 2020a;Castillo and Treon, 2020;Owen et al, 2020), which bodes well for additional FDA approval of acalabrutinib in the treatment of WM. A number of ongoing clinical trials are evaluating the effects of acalabrutinib, as monotherapy or in combination therapies with other regimens, in patients with DLBCL (monotherapy or in combination with R-CHOP, KRT-232 or vistusertib), FL (in combination with rituximab or pembrolizumab), MZL (in combination with tafasitamab), MM (monotherapy or in combination with dexamethasone), B-ALL (in combination with ACP-319), posttransplant LPD (in combination with rituximab), PCNSL and SCNSL (in combination with durvalumab) 1 .…”
Section: Introductionmentioning
confidence: 80%
“…A recent study shows that overexpression of CXCR4 in CD8+ T-cells redirects them to CXCR12+ cells in the BM vascular niche and promotes their memory differentiation and anti-tumor response ( Khan et al, 2018 ). Instead, use of CXCR4-targeting agents holds promise for treatment of the patients with B-cell lymphomas including WM ( Castillo and Treon, 2020 ). Chemotherapeutic agent, such as ibrutinib that targets B-cell receptor signaling and is used in the treatment of certain B-cell lymphomas could also interfere with the interaction of tumor cells with the BM niche.…”
Section: Clinical Relevancementioning
confidence: 99%